Final validation of the ProMisE molecular classifier for endometrial carcinoma in a large population-based case series - Kommoss, Stefan; Kommoss, Felix (Annals of oncology, 2018)
We have previously developed and confirmed a pragmatic molecular classifier for endometrial cancers; ProMisE (Proactive Molecular Risk Classifier for Endometrial Cancer). Inspired by the Cancer Genome Atlas, ProMisE identifies four prognostically distinct molecular subtypes and can be applied to diagnostic specimens (biopsy/curettings) enabling earlier informed decision-making. We have strictly adhered to the Institute of Medicine (IOM) guidelines for the development of genomic biomarkers, and herein present the final validation step of a locked-down classifier before clinical application.
Gesehen am 16.12.2019